Health Literacy in Male-Dominated Occupations. Issue 5 (October 2020) - Milner, Allison; Shields, Marissa; Scovelle, Anna J.; Sutherland, Georgina; King, Tania L.
Low levels of health literacy are associated with poorer health outcomes. Both individual- and social-level factors have been identified as predictors of low health literacy, and men are known to have lower health literacy than women. Previous research has reported that men working in male-dominated occupations are at higher risk of accidents, injury, and suicide than other population groups, yet no study to date has examined the effect of gendered occupational contexts on men's health literacy. The current article examined the association between occupational gender ratio and health literacy among Australian males. The Australian Longitudinal Study on Male Health (Ten to Men) was used to examine associations between occupational gender ratio (measured in Wave 1) and health literacy (measured in Wave 2) across three subscales of the Health Literacy Questionnaire. Multivariable linear regression analyses were used and showed that the more male dominated an occupational group became, the lower the scores of health literacy were. Results for the different subscales of health literacy for the most male-dominated occupational group, compared to the non-male-dominated group were: ability to find good health information, (Coef. −0.80, 95% CI [−1.05, −0.54], p < .001); ability to actively engage with health-care providers, (Coef. −0.35, 95% CI [−0.62, −0.07], p = .013); and feeling understood and supported by health-care providers, (Coef. −0.48, 95% CI [−0.71, −0.26], p = < .001). The results suggest the need for workplace interventions to address occupation-level factors as an influence on health literacy among Australian men, particularly among the most male-dominated occupational groups.